Secondary School Counsellor Qualifications in British Columbia - Green, Lynne; Banmen, John (Canadian Journal of Counselling and Psychotherapy, 2012)
Through the use of a questionnaire to all school districts in British Columbia,data were gathered on various aspects of school counselling. Respondents covered areas such as counsellor qualification standards, selection criteria, up-grading, centralized decision making, uniformity in standards, and present counsellor qualifications.The findings indicate support for more centralized standards and greater support for up-grading, since less than half of the practicing counsellors meet theminimum qualification, and strong support to have various groups such as Universities,Ministry of Education, school districts and the B.C. School CounseUors'Association work together to bring about a large number of improvements. Thestudy was a follow-up to the Ministry of Education's Task Force Report onSecondary School Counselling.